Chemistry of guanidinate‐stabilised diboranes: transition‐metal‐catalysed dehydrocoupling and hydride abstraction - Wagner, Arne; Litters, Sebastian; Elias, Jana; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2014)
Click or tap to learn more.
Gesehen am 07.08.2020